2011
DOI: 10.3892/etm.2011.234
|View full text |Cite
|
Sign up to set email alerts
|

Detection of circulating tumor cells: Clinical relevance of a novel metastatic tumor marker

Abstract: Abstract. most cancer-related deaths are caused by the hematogenous spread of cancer cells to distant organs and their subsequent metastasis. during the early stages of the metastatic cascade, cancer cells disseminate from the primary site via the lymphatic vessels and/or by hematogenous routes. circulating tumor cells (ctcs), cancer cells that have disseminated into the systemic circulation, may be a predictor of poor prognosis in several carcinomas. an understanding of the molecular mechanisms involved in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 83 publications
0
8
0
Order By: Relevance
“…It is clear that enrichment steps are necessary to increase the detection of such rare cells. 11 At present, normal and apoptotic cells were rare. 5-FU (20 μmol/L) was added to the PL45 cells and incubated for 12 and 24 h, and subsequently the number of apoptotic cells were found to be noticeably increased ( Fig.…”
Section: Detection Of Apoptotic Circulating Tumor Cells In Advanced Pmentioning
confidence: 84%
“…It is clear that enrichment steps are necessary to increase the detection of such rare cells. 11 At present, normal and apoptotic cells were rare. 5-FU (20 μmol/L) was added to the PL45 cells and incubated for 12 and 24 h, and subsequently the number of apoptotic cells were found to be noticeably increased ( Fig.…”
Section: Detection Of Apoptotic Circulating Tumor Cells In Advanced Pmentioning
confidence: 84%
“…The FDA approved The CellSearch System, and novel microfluidic chips methods are used to increase the sensitivity and specificity of the CTC detection . Malignant feature of CTCs can be validated by amplification or deletion of genes and chromosomes in different kinds of solid cancer . It may be important to include CTC measurements in TNM stage in BC to improve quality of life or increase survival by aiding decision making with respect to therapeutic strategy in the near feature.…”
Section: Ctcs Can Be Used As a Novel Marker To Determine Tailored Thementioning
confidence: 99%
“…5,100,102,103 Malignant feature of CTCs can be validated by amplification or deletion of genes and chromosomes in different kinds of solid cancer. 19,33,34,[139][140][141] It may be important to include CTC measurements in TNM stage in BC to improve quality of life or increase survival by aiding decision making with respect to therapeutic strategy in the near feature.…”
Section: Ctcs Can Be Used As a Novel Marker To Determine Tailored Thementioning
confidence: 99%
“…Although CTCs have been extensively studied for more than two decades, there are few reliable methods of detecting and isolating CTCs in the early stages of cancer. [19][20][21] Experimental in vivo studies have suggested that CTCs are present early in the natural history of solid tumor growth, before the development of metastasis. 22 More recently, CTCs have been detected in the blood at early stages and at recurrence in women with breast cancer, 14,23 and in premalignant stages of prostate cancer tumor progression.…”
Section: Introductionmentioning
confidence: 99%